2002
DOI: 10.2307/3285391
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum and P. vivax Gametocyte-Specific Exoantigens Stimulate Proliferation of TCR γδ + Lymphocytes

Abstract: Immune modulation of Plasmodium vivax and P. falciparum gametocytes occurs over the course of erythrocytic infection. The response is linked to proliferative and inflammatory responses, which may be stimulated by stage-specific gametocyte proteins. Stage-specific exoantigens were purified from supernatants of P. falciparum and P. vivax gametocyte cultures, and either primary or secondary postinfection lymphocytes were stimulated for proliferation. Five of 25 exoantigens purified from P. falciparum gametocyte c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…[63][64][65][66][67][68] The depletion of ␥␦ ⌻ cells has proved to dramatically reduce the severity of rheumatoid arthritis in a mouse model. 58 Furthermore, Plasmodium falciparum exoantigens have been shown to stimulate the proliferation of ␥␦ T-lymphocytes in patients after primary infection, 69 and accumulations of these cells have been observed in the spleens and peripheral blood of patients with P falciparum malaria. 2,70 Finally, ␥␦ ⌻ cells, which are known to participate in the immune response to several viruses, 71 can respond in vitro to EBV-infected human Burkitt cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…[63][64][65][66][67][68] The depletion of ␥␦ ⌻ cells has proved to dramatically reduce the severity of rheumatoid arthritis in a mouse model. 58 Furthermore, Plasmodium falciparum exoantigens have been shown to stimulate the proliferation of ␥␦ T-lymphocytes in patients after primary infection, 69 and accumulations of these cells have been observed in the spleens and peripheral blood of patients with P falciparum malaria. 2,70 Finally, ␥␦ ⌻ cells, which are known to participate in the immune response to several viruses, 71 can respond in vitro to EBV-infected human Burkitt cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Parasite factors such as surface proteins and secretory molecules can directly suppress the function of certain subsets of immune cells as well as stimulate other cell populations that have suppressive activity like the regulatory T cells (43). A previous study has reported that P. falciparum and Plasmodium vivax gametocyte-specific exoantigens stimulate proliferation of T cell receptor ␥␦ ϩ lymphocytes (44). The LCCL family of Apicomplexaspecific proteins (PfCCP1 in our data) has also been reported to play a role in host immune evasion (23).…”
Section: Discussionmentioning
confidence: 99%
“…␥ 9 ␦ 2 T cells proliferate and develop relevant effector functions in response to M. tuberculosis (15), HIV (16), Plasmodium spp. (17), and many other human pathogens (18)(19)(20)(21)(22). Furthermore, depletion of circulating ␥ 9 ␦ 2 T cells during infections with different pathogens has been associated with increased susceptibility to more severe disease (23)(24)(25).…”
mentioning
confidence: 99%